Village Fund Management and Determinants of Socio-Economic Welfare Level of Village Communities in Pringgabaya District - East Lombok - Wahyunadi; St Maryam; Mansur Afifi; Ihsan Rois (Jurnal Ekonomi, 2024)
This study is intended to test the effect of village fund management through the variables of Transparency and Accountability partially and simultaneously on the level of Community Welfare in Pringgabaya District. This study is a quantitative study. The sample in this study was obtained using a purposive sampling method with a total of 100 respondents with different educational backgrounds, jobs and positions. The data used in the study are primary data in the form of questionnaires filled out directly by the respondents. The analysis method used is multiple regression analysis with the SPSS application tool. The results of this study indicate that the Transparency variable in village fund management has a positive effect on community welfare, and the Accountability variable in village fund management has a positive and significant effect on community welfare.